Perforated isolated jejunal diverticulum: a rare aetiology of acute abdomen. (11th March 2014) - Baksi, Aditya; Gupta, Shahana; Kumar, Sanjeev; Ray, Udipta
Abstract : In the absence of trauma, perforated jejunal diverticulum (JD) is a rare entity. Perforated isolated JD is rarer. We report a case of perforated isolated JD in a 55-year-old woman who presented with features of peritonitis and had no history of trauma. Resection and anastomosis of the involved jejunal segment was performed.